Relationship of Knowledge, Attitude and Behavior toward Dental Caries in Children : Hubungan Pengetahuan, Sikap dan perilaku terhadap Karies Gigi pada Anak - Euis Sartika; Nur Juliana; Harnianti; Andyka; Lisna (Politeknik Karya Persada Muna, 2022)
Background: Dental caries is still a major problem in oral health. Poor or inadequate dental care causes the most common of all dental health problems in childhood. The prevalence of caries in early childhood, which is in the age range of 3-4 years is 82%, meaning that only 18% of Indonesian children are free from dental caries. Methods: This research method is a Literature review. The Literature Review uses accredited databases such as Google Scholar, Pubmed, and Garuda and screening from 2017-2022, starting with identifying relevant keywords and synonyms. The journal search succeeded in obtaining 78 journals so 20 journal articles were screened from national and international journals. Results: The results of the analysis of the articles that have been screened show that 16 journal articles have a relationship between knowledge, attitudes, and behavior toward dental caries. This means that the better the knowledge, attitudes, and behavior, the better the dental and oral health in children, and the less the incidence of dental caries that will occur. Meanwhile, 4 journal articles are showing no relationship between knowledge, attitude, and behavior toward dental caries. Conclusion: Knowledge, attitude, and behavior of children about dental health in the good category showed that there was a significant relationship with dental caries. Keyword: Knowledge, Attitude, Behaviour Denta Cariers, Children